PENERAPAN MODEL PEMBELAJARAN PENEMUAN (DISCOPERY LERNING) DAN METODE DEMONTRASI DAPAT MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS VI DI SD NEGERI 022 TAMBUSAI - Tommi Sari (Indonesian Journal of Basic Education, 2019)
This study aims to improve science learning outcomes by applying the Demonstration Method for Grade VI students of the second semester at SDN 022 Tambusai, Rokan Hulu Regency. The instruments used in the CAR consisted of observations and test questions. The sample in this study were all 6th grade students, totaling 25 children. The results obtained in this study were an increase in the completeness of the evaluation results of students towards understanding the energy material and its changes. The increase in students' mastery learning occurred gradually, where the initial conditions of student motivation were still very low, after the Classroom Action Research, the first cycle of students with high motivation was 17 students (60%) ,. Cycle II students with high motivation 24 students (94%), and low motivation 1 student (5%). The completeness rate in the initial study was 33%, cycle I 60% and cycle II 95%. From the results of this research, a teacher should be able to manage the learning process by applying methods that fit the material, one of which is the demonstration method